Analisis Pengaruh Variabel Makro Terhadap IHSG di Indonesia Periode 2010 Sampai 2021 - Heri Sasono; Nurhanan Said (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The joint stock price index (IHSG) as a benchmark for the progress of the capital market in Indonesia. The purpose of this study was to analyze the effect of Macro Variables on the Composite Stock Price Index (JCI) for the period 2010 to 2021. The macro variables used were Inflation, Economic Growth, Dollar Exchange Rate and SBI or 7 Day Repo Rate against the JCI. The number of years in the sample is 12 years, from 2010 to 2021. Multiple linear regression analysis, T test, F test, coefficient of determination test using SPSS Version 26 software. The conclusion is that gold price and Lq45 has significant effect on the JCI, while the others macro variable, have no significant effect on the JCI. Simultaneously, all macro variables have a significant effect on the JCI.